Adult-onset Still's disease with neurological involvement: a single-centre report. (28th December 2020) - Zhao, Mengzhu; Wu, Di; Shen, Min
Abstract: Objectives: Adult-onset Still's disease (AOSD) is a multifactorial systemic autoinflammatory disease. Neurological damage has been rarely reported in AOSD. We aimed to characterize the clinical features of AOSD patients with neurological involvement. Methods: A total of 187 AOSD patients were admitted to Peking Union Medical College Hospital from January 2015 to August 2019. The complete medical records were reviewed in this retrospective study. Clinical features of 14 AOSD patients with neurological involvement were collected and compared with those without. Results: The prevalence of neurological involvement in AOSD inpatients was 7.5%. The median disease duration was 4.5 months, with a range of 1–15 months. The frequent symptoms were fever [14 (100%)], rash [13 (92.9%)], liver dysfunction [11 (78.6%)], arthralgia/arthritis [10 (71.4%)] and lymphadenopathy [10 (71.4%)]. Four (28.6%) patients had macrophage activation syndrome (MAS). Aseptic meningitis was the most common presentation (64.3%) when the nervous system was involved. Other rare manifestations included cranial nerve palsy, encephalitis and cerebral infarction. The rate of MAS, serum levels of lactate dehydrogenase and ferritin were significantly higher in AOSD patients with neurological involvement than in those without. All patients received high-dose corticosteroid therapy and immunosuppressive agents and two were given tocilizumab. Clinical remission was achieved in all 14 AOSD patients with neurological involvement. Conclusion: Neurological involvement, particularly aseptic meningitis, is not a rare complication of AOSD. It is frequently complicated by MAS. There may be a potential relationship between the neurological damage of AOSD and MAS.